2021
DOI: 10.3390/ijms22147478
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effect of the Phenotype of Tumour-Associated Macrophages, Regulated by CD39, on Colon Cancer in Mice

Abstract: Background: This study was designed to investigate the effect of cluster differentiation (CD)39 and CD73 inhibitors on the expresion of tumour-associated macrophages (TAMs), M1- versus M2-tumour phenotypes in mice with colon cancer. Methods: An in vivo study of co-culture with colon cancer cells and immune cells from the bone marrow (BM) of mice was performed. After the confirmation of the effect of polyoxotungstate (POM-1) as an inhibitor of CD39 on TAMs, the mice were randomly divided into a control group wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…7 Park et al showed that administration of POT-1, the inhibitor of CD39, prevents colon cancer cells growth in mice and increases M1-phenotype macrophages in cancer tissue. 29 In present study, CD39 mRNA expression decreased after treatment with DHA, but its controlling miRNA, mir-142 increased in both HT-29 and Caco-2 cell lines. In this way, DHA through regulating CD39, may be effective in controlling CRC metastasis.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…7 Park et al showed that administration of POT-1, the inhibitor of CD39, prevents colon cancer cells growth in mice and increases M1-phenotype macrophages in cancer tissue. 29 In present study, CD39 mRNA expression decreased after treatment with DHA, but its controlling miRNA, mir-142 increased in both HT-29 and Caco-2 cell lines. In this way, DHA through regulating CD39, may be effective in controlling CRC metastasis.…”
Section: Discussionsupporting
confidence: 47%
“…Künzli et al reported that survival duration in CRC tumors expressing a low level of CD39 was high and associated with less invasion 7 . Park et al showed that administration of POT‐1, the inhibitor of CD39, prevents colon cancer cells growth in mice and increases M1‐phenotype macrophages in cancer tissue 29 . In present study, CD39 mRNA expression decreased after treatment with DHA, but its controlling miRNA, mir‐142 increased in both HT‐29 and Caco‐2 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Both drugs are currently undergoing clinical trials (NCT03884556, NCT04306900, and NCT04261075). Polyoxotungstate, an inhibitor of CD39, has been shown to increase the levels of M1 anti-tumor macrophages as well as CD8 + T cells and significantly inhibit the growth of CT26 colon cancer ( 178 ). AB680, a selective CD73 inhibitor, induced the proliferation and cytotoxic activity of depleted CD8 + T cells and significantly inhibited the growth of colon cancer established by CT26 cells; moreover, it exhibited favorable pharmacokinetic properties.…”
Section: Cd39/cd73 Axismentioning
confidence: 99%
“…Immune checkpoint inhibitors have improved the treatment of cancer. However, many cancers do not respond to immunotherapy or develop resistance to therapy; therefore, efforts have been made to identify new targets and drugs that can improve the antitumor immune response [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…CD39 is an ectoenzyme that degrades adenosine triphosphate and adenosine diphosphate into adenosine monophosphate [7,8]. CD73, expressed on the cell surface, degrades adenosine monophosphate into ADO [1][2][3].…”
Section: Introductionmentioning
confidence: 99%